Common fixed point theorems for two pairs of self-mappings in complex-valued metric spaces - Rouzkard, Fayyaz (Eurasian Mathematical Journal, 2019)
In this paper, we consider complex-valued metric space and prove some coincidence point and common fixed point theorems involving two pairs of self-mappings satisfying the contraction condition with complex coefficients in these spaces. In this paper, we generalize, improve and simplify the proofs of some existing results.